INCIDÊNCIA DAS HEMOGLOBINOPATIAS EM RECÉM-NASCIDOS DO ESTADO DE MATO GROSSO DO SUL - PATRICIA MEDEIROS SILVA GRILO (2021)
Hemoglobinopathies are considered the most common genetic diseases in the world and early diagnosis is made through the Biological Neonatal Sorting or Foot Test. Studies of abnormal hemoglobin frequencies allow evaluating the behavior of altered genes in each population and defining health management strategies. The aim of this study was to evaluate the incidence of the hemoglobinopathies in newborns from the Mato Grosso do Sul state screened by The Association of Parents and Friendsof the Exceptional and the Institute of Research Teaching and Diagnosis, center responsible for biological neonatal sorting of the state. Observational, cross-sectional, descriptive and quantitative study was performed for 16 months between April 2019 and July 2020 and all newborns with abnormal hemoglobins were worth it. Electrophoretic, chromatographic and molecular analyses were used for sorting and completion of diagnosis with the support of the Genetics Laboratory of the Federal University of Tres Lagoas. In the period studied, 56,998 children were born in the state of MS and 47,879 were screened (coverage of 84%). Of the newborns screened, 1,254 (2.6%) had an abnormal hemoglobin profile resulting in an incidence of 1 in 45 alive neonates. Among the Hb variants in heterozygosis were found the profiles FAS (73.2%), FAC (22.4%), FAD-Los Angeles (0.4%), FAE (0.2%), FAB2 (0.2%), FA/Korle Bu (0.1%), FA/Osu-Christiansborg (0.1%), FA/Etobicoke (0.1%), and FA/Hasharon (0.1%). Alpha thalassemia was found in association with the FAS and FAC profiles with the incidence of 1:2.478 neonates and beta thalassemia in C/Beta+ thalassemia cases with 1:14,249 neonates. In the Tres Lagoas health macro-region, the incidence of abnormal hemoglobins was 33 cases/1000 neonates, in the Corumba with 28 cases/1000 neonates, Campo Grande with 20 cases/1000 neonates and Dourados with 19.7/1000 neonates. On the incidence of Hb S, the sickle cell trait was 1:62 neoantes and Sickle Cell Disease 1:4.749 neonates. Regarding the average of days between the Birth Date (DN) and the Collection Date (DC), it was found that 57% of the samples were collected between the 3rd and 5th of life and 6.6% of the collections outside the period recommended by the PNTN. Between DC and Analysis Date, the average was 12.2 days. Finally, the average of days between the date of birth and the date of analysis was 21.6 days (minimum 4 and maximum 451 days) and no difference was obtained between the health macro-regions. The results obtained in this study ensure the construction of epidemiological data of hemoglobinopathies in Mato Grosso do Sul allowing the evaluation of the distribution of abnormal hemoglobins, the diagnosis of heterozygotes and the possibility of genetic counseling. It is recommended that, in the education of nurses, the diseases detected by biological neonatal sorting, specifically hemoglobinopathies, be emphasized, because it is the professionals who are present from prenatal care to birth. Keywords: Early diagnosis, Thalassemia, Sickle Cell Disease, High Efficiency Liquid Chromatography.